Changes in ecosystem structure, function and hydrological connectivity control water, soil and carbon losses in semi‐arid grass to woody vegetation transitions. Issue 13 (11th July 2013) - Puttock, Alan; Macleod, Christopher J.A.; Bol, Roland; Sessford, Patrick; Dungait, Jennifer; Brazier, Richard E.
ABSTRACT Connectivity has recently emerged as a key concept for understanding hydrological response to vegetation change in semi‐arid environments, providing an explanatory link between abiotic and biotic, structure and function. Reduced vegetation cover following woody encroachment, generally promotes longer, more connected overland flow pathways, which has the potential to result in an accentuated rainfall‐runoff response and fluxes of both soil erosion and carbon. This paper investigates changing hydrological connectivity as an emergent property of changing ecosystem structure over two contrasting semi‐arid grass to woody vegetation transitions in New Mexico, USA. Vegetation structure is quantified to evaluate if it can be used to explain observed variations in water, sediment and carbon fluxes. Hydrological connectivity is quantified using a flow length metric, combining topographic and vegetation cover data. Results demonstrate that the two woody‐dominated sites have significantly longer mean flowpath lengths (4 · 3 m), than the grass‐dominated sites (2 · 4 m). Mean flowpath lengths illustrate a significant positive relationship with the functional response. The woody‐dominated sites lost more water, soil and carbon than their grassland counterparts. Woody sites erode more, with mean event‐based sediment yields of 1203 g, compared to 295 g from grasslands. In addition, the woody sites lost more organic carbon, with mean event yields of 39 g compared to 5 g from grassland sites. Finally, hydrological connectivity (expressed as mean flowpath length) is discussed as a meaningful measure of the interaction between structure and function and how this manifests under the extreme rainfall that occurs in semi‐arid deserts. In combination with rainfall characteristics, connectivity emerges as a useful tool to explain the impact of vegetation change on water, soil and carbon losses across semi‐arid environments. Copyright © 2013 John Wiley & Sons, Ltd.